Knowledge perception and practices of mothers of children with Hydrocephalus and Shunt complications at Queen Elizabeth Central Hospital - Nkhambule, Ndaona Regina (Kamuzu University of Health Sciences, 2022)
This study was conducted to explore the knowledge perception and practices of mothers of children with hydrocephalus and shunt complications at QECH. Specifically, the areas of interest were: to assess knowledge of mothers on hydrocephalus and VP Shunt, to describe the mother's beliefs related to hydrocephalus, to identify challenges faced by mothers of children with hydrocephalus and to assess mother's psychosocial responses to children with hydrocephalus. The study was conducted at Queen Elizabeth Central Hospital, surgical Pediatric Ward. A qualitative research design was used and 10 mothers of children with hydrocephalus were selected using convenience sampling. Data was collected through an in-depth interview using questionnaire. Data was analysed using manually and categorized. The study has revealed that the birth of an abnormal infant created a crisis situation that gave rise to grief reactions to the mothers. The results have also shown that these mothers have knowledge on what hydrocephalus is and how it is treated at the hospital. Despite having the knowledge of the condition these mothers encountered several challenges in the course of bringing up their children. Their interpersonal relationships were disturbed with the birth of the malformed children and beliefs in witchcraft have played a part in stigma or discrimination from their communities. However, hope and belief in God assisted them to cope with the situation. The children's improvement gave the mothers hope that their children were going to be alright in the future. Basing on the findings, this study recommends the nurses should advise and encourage mothers to be coming to the hospital as soon as they can whenever the child is sick, for shunt revisit or when they see early signs of shunt complications and that Community health nurses should educate the community members including the leaders and other prominent people about hydrocephalus and its complications to prevent stigmatization.